A proposed field emergency donor panel questionnaire and triage tool. (April 2016) - Doughty, Heidi; Thompson, Patrick; Cap, Andrew P.; Spinella, Philip C.; Glassberg, Elon; Skogrand Eliassen, Håkon; De Pasquale, Marc; Strandenes, Geir
Abstract : BACKGROUND: The provision of transfusion support to isolated military or civilian projects may require the use of an emergency donor panel (EDP) for immediate warm fresh whole blood (WFWB). The aim of this short discussion article is to raise and resolve some of the practical aspects for the nonspecialist faced with the emergency collection of WFWB whole blood in the austere medical environment (AME). METHODS AND RESULTS: A proposed field EDP questionnaire and triage tool (QTT) is presented. It is designed for the hostile, remote, or austere environment that falls outside normal regulated supply of cold‐stored blood products or removed from trained blood collection personnel, where collection may fall to an isolated medical provider. The tool has been drafted based on review of existing guidelines and consultation with practitioners. It serves as a point of reference for local guidelines and has yet to be validated. CONCLUSIONS: The use of the EDP is associated with risk; however, it remains the simplest method of providing rapid transfusion support. The best way to manage the risk is to brief and prescreen blood donors before deployment. An abbreviated donor QTT can be an aide to decision making at the time of donation. The tool should be tailored to requirements and underpinned by policy and training.